The role of interactive radio programs in enhancing the meanings of the Amazigh language in its Chaoui variety: an analytical study of the program “Sili Mahtsilidh” on Radio Algeria from Khenchela - Bourouabhiya, Fawaz; sahatal, ibtissam (El Omda in Linguistics and Discourse Analysis, 2025)
This research aimed to identify the relationship between interactive radio programs and the processes of instruction and learning, as well as the stimulation of linguistic practice in spoken form regarding all aspects of the Amazigh language—its rules, terminology, and meanings in its Chaoui variety. Radio broadcasting is no longer merely a medium for transmitting information; it has shifted from being a media institution concerned with information dissemination to playing the role of a teacher or instructor, by stimulating spoken Amazigh linguistic practice in its Chaoui variant, starting with the expansion of oral language learning to a wider audience. The researcher adopted a survey methodology and selected a purposive sample using a sampling survey approach. The study found that the interactivity embedded in the program significantly contributed to enriching the Amazigh language in its linguistic variant through the flow of information between the program producer and the audience. The program requires specialists in the written Amazigh language to ensure the accuracy of the information circulated within it, as well as linguistics experts to give the program academic credibility and ensure the correctness of the linguistic meanings of Amazigh in its Chaoui variety.